2018
DOI: 10.1634/theoncologist.2018-0542
|View full text |Cite
|
Sign up to set email alerts
|

Apatinib for Advanced Osteosarcoma after Failure of Standard Multimodal Therapy: An Open Label Phase II Clinical Trial

Abstract: Background Antiangiogenesis tyrosine kinase inhibitors (TKIs) have been shown to prolong progression‐free survival (PFS) in advanced osteosarcoma. Methylsulfonic apatinib is a TKI that specifically inhibits vascular endothelial growth factor receptor‐2. We aim to assess apatinib in patients with advanced high‐grade osteosarcoma progressing upon chemotherapy. Materials and Methods This phase II trial was conducted at Peking University People's Hospital. We enrolled participants (≥16 years of age) with progressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
111
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 102 publications
(123 citation statements)
references
References 30 publications
12
111
0
Order By: Relevance
“…However, several clinical studies of selective inhibitors, such as imatinib, demonstrated little or no activity as a single agent in OS [23,24]. On the other hand, several clinical trials of multiple TK inhibitors, such as regorafenib [25], cabozantinib [26], and apatinib [27], in OS indicated a marked effect for OS and the potential to be developed as new therapeutic agents. TAS‐115 is also a novel multiple RTK inhibitor that demonstrates much less toxicity in various normal cell lines than other VEGFR‐targeted kinase inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…However, several clinical studies of selective inhibitors, such as imatinib, demonstrated little or no activity as a single agent in OS [23,24]. On the other hand, several clinical trials of multiple TK inhibitors, such as regorafenib [25], cabozantinib [26], and apatinib [27], in OS indicated a marked effect for OS and the potential to be developed as new therapeutic agents. TAS‐115 is also a novel multiple RTK inhibitor that demonstrates much less toxicity in various normal cell lines than other VEGFR‐targeted kinase inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…Baseline characteristics have been reported. 27 The overall incidence of apatinib-related AEs was 89.2%. In general, drug-related AEs were limited to grade one or two.…”
Section: Summary Of Aesmentioning
confidence: 97%
“…With a median follow-up time of 7.37 months (interquartile range [IQR], 6.33-11.07) for the safety analysis, 22/37 (59.5%) patients had dose-reduced treatment, and 11/37 (29.7%) patients had temporary treatment interruption. 27 The frequency of apatinib administration was 40.5% of the planned administration dose. Due to the small sample size, we did not observe some rarely seen AEs (overall incidence ≤5% of patients) and merged some of the AEs into one bigger group for more appropriate statistical analyses.…”
Section: Summary Of Aesmentioning
confidence: 99%
See 1 more Smart Citation
“…In China, apatinib has been approved for the thirdline treatment of advanced gastric adenocarcinoma and adenocarcinoma in the gastric-esophageal junction (7)(8)(9). Moreover, multiple studies have demonstrated its use in patients with other advanced malignancies, such as breast cancer (10,11), hepatic carcinoma (12), lung cancer (13,14), colorectal cancer (15), and soft tissue tumors (16,17). Case reports and clinical studies have also illustrated the e cacy and safety of apatinib in recurrent OC (18)(19)(20)(21)(22); however, to our knowledge, its e cacy in biochemical recurrent patients is not yet known.…”
Section: Introductionmentioning
confidence: 99%